Global Research Trends on Early-Life Feeding Practices and Early Childhood Caries: A Systematic Review. (19th May 2014) - Chaffee, Benjamin W.; Cheng, Ashley
Abstract : Objective . To describe the epidemiologic literature related to early-life feeding practices and early childhood caries (ECC) with regard to publication attributes and trends in these attributes over time. Methods . Systematic literature review including electronic and manual searches (in BIOSIS, CINAHL, Cochrane Library, LILACS, MEDLINE, Web of Science, and WHOLIS), covering the years 1990–2013. Attributes of publications meeting a priori inclusion criteria were abstracted and organized by global region and trends over time. Attributes included country of origin and study design of included publications and age and caries prevalence of the populations studied. Results . 244 publications drawn from 196 independent study populations were included. The number of publications and the countries represented increased over time, although some world regions remained underrepresented. Most publications were cross-sectional (75%); while this percentage remained fairly constant over time, the percentage of studies to account for confounding factors increased. Publications varied with respect to the caries experience and age range of children included in each study. Conclusions . Publication productivity regarding feeding practices and ECC research has grown, but this growth has not been evenly distributed globally. Individual publication attributes (i.e., methods and context) can differ significantly and should be considered when interpreting and synthesizing the literature.